Sosialisasi Penyelenggaraan Rekam Medis dalam Pemenuhan Standar Akreditasi di Klinik Pratama Padang - Alfita Dewi (Stikes Syedza Saintika Padang, 2023)
Clinic is a health service facility that organizes individual health services that provide basic and/or specialist medical services. In providing patient health services, clinics need a medical record unit that is responsible for managing patient data into useful information for decision making. Medical records aim to support the achievement of orderly administration in the context of efforts to improve health services, medical record services are one of the supporting services that must be carried out in health facilities, one of which is a clinic. This Community Service (PKM) was carried out on February 9, 2023. This Community Service activity was carried out by providing socialization regarding the implementation of medical records to partners. The team provided basic understanding regarding medical records such as the basic rules for administering medical records. The RM implementation system at the clinic is running well, but the implementation is not optimal because it is still not in accordance with the standards for organizing medical records. There is an increase in the knowledge of medical record officers after being given socialization. Keywords: medical records, accreditation standards, pratama clinics